Pengaruh CSR, Transfer Pricing, Inventory Intensity Terhadap Tax Avoidance - Feni Nur Solihati; Lidya Agustina (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
Tax avoidance remains a critical issue affecting government revenue in Indonesia, particularly in the manufacturing sector, which accounts for 25.2%–30% of tax revenue. This study examines the influence of Corporate Social Responsibility (CSR), Transfer Pricing, and Inventory Intensity on Tax Avoidance in manufacturing companies listed on the Indonesia Stock Exchange during 2019–2023, as well as its application in the field of education. Using a quantitative methodology with multiple linear regression analysis on 130 observations from 28 companies selected via purposive sampling, the results indicate that CSR has a positive and significant effect on tax avoidance. Transfer pricing exhibits a negative effect on tax avoidance, suggesting that higher transfer pricing transactions lead to lower tax avoidance. However, Inventory Intensity does not significantly influence tax avoidance. This model explains 53.8% of the variability in tax avoidance. These findings contribute to understanding corporate behavior regarding tax compliance and provide practical implications for policymakers in strengthening tax regulations and oversight mechanisms in Indonesia’s manufacturing sector, as well as educational implications for students.